2023
DOI: 10.21873/invivo.13251
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Antineoplastic Nanocarriers on 3D Oral Cancer Spheroids

NANCY LETICIA MENDOZA-MARTINEZ,
AYLIN DIVINA CADENA-GALEANA,
FRANCISCO GERMAN VILLANUEVA-SANCHEZ
et al.

Abstract: Background/Aim: Cancer is a leading cause of death worldwide. Conventional treatments as surgery, chemotherapy, radiotherapy, and combined therapies are commonly used. However, these therapies have several limitations and side effects. To address these issues, innovative research is being conducted on nanocarriers (NCs) functionalized with antineoplastic agents. These NCs aim to overcome limitations and improve patients' lives. However, before they can be used clinically, these NCs are primarily assessed on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…For this reason, the SEM images of MgO nanoparticles were obtained at different magnifications depicted in Figure 2a,b. In Figure 2a, the morphology of the MgO was observed and revealed that the particles were spheroids with round ends and joined at different points and with smooth surfaces [18]. These results show that some of the particles are dispersed entirely, and some of them are aggregated.…”
Section: Sem Analysismentioning
confidence: 86%
“…For this reason, the SEM images of MgO nanoparticles were obtained at different magnifications depicted in Figure 2a,b. In Figure 2a, the morphology of the MgO was observed and revealed that the particles were spheroids with round ends and joined at different points and with smooth surfaces [18]. These results show that some of the particles are dispersed entirely, and some of them are aggregated.…”
Section: Sem Analysismentioning
confidence: 86%